Robot Sebagai Sumber Ide Motif Batik Kontemporer dengan Teknik Malam Dingin - Arief Satriyo Wibowo (Besaung : Jurnal Seni Desain dan Budaya, 2026)
The design of contemporary batik motifs represents an innovative effort to expand the potential of batik as a medium of expression that adapts to contemporary cultural and technological developments. This project combines traditional batik elements with contemporary technology-themed visuals by presenting humanoid robot imagery as the main motif, supported by robot characters, technological components, and mechanical elements. The visual development adapts the rigid form of robots with warm retro color tones, creating dynamic and narrative visual patterns that reflect a modern aesthetic. The design is applied using a full-repeat one-step pattern system specifically targeted at teenage male consumers. The repetitive pattern arrangement produces a catchy, playful, and casual visual impression that aligns with the preferences of youth who tend to favor unique, exclusive products with strong visual identities. The production process employs a cold wax screen-printing technique, a batik waxing method using screen printing tools that enables more efficient motif detailing. This technique also offers a distinctive characteristic, as it remains relatively unfamiliar among traditional batik artisans. The results indicate that robot-themed batik motifs have strong potential as visual innovations for development within the creative and fashion industries. This design approach not only introduces new aesthetic expressions but also opens opportunities for batik to become more relevant to younger generations while strengthening cultural sustainability in the modern era